Persepsi Guru IPS terhadap Pelaksanaan Kurikulum Merdeka Belajar di SMP Negeri Kecamatan Tanjung Kemuning Kabupaten Kaur - Wingsi ANGGILA; Adisel Adisel; Salamah Salamah (Indonesian Journal of Social Science Education (IJSSE), 2023)
This study aims to describe the Planning of Social Sciences Study Teachers in the Implementation of the Independent Learning Curriculum at State Junior High Schools in Tanjung Kemuning District, Kaur Regency. This research is a field research with a descriptive qualitative approach. The data sources of this study were 3 principals, 4 social studies teachers, 3 school representatives, 6 peer teachers. Data collection techniques in this study were carried out by observation, interviews, and documentation. The data analysis technique uses data reduction, data display, and verification. The results of the study found that the results of the study also explained the importance of massive socialization to all parties at the education unit level, so that curriculum implementation could be carried out properly in accordance with expectations. In addition, the perception of social studies teachers has several indicators in implementing the independent learning curriculum, including reducing curriculum content, constructivism learning, teacher personal experience and teacher education degrees. There are several factors that become obstacles, namely, the first is the quality of human resources of the teachers who are not adequate, secondly the facilities and learning resources are minimal or the infrastructure is inadequate and the teachers are clueless, the three teachers are comfortable with the old standards and have no experience in learning. free to learn.